Hydrogen Sulfide Donor Protects Porcine Oocytes against Aging and Improves the Developmental Potential of Aged Porcine Oocytes - Krejcova, Tereza (PLoS One, 2015)
Porcine oocytes that have matured in in vitro conditions undergo the process of aging during prolonged cultivation, which is manifested by spontaneous parthenogenetic activation, lysis or fragmentation of aged oocytes. This study focused on the role of hydrogen sulfide (H(2)S) in the process of porcine oocyte aging. H(2)S is a gaseous signaling molecule and is produced endogenously by the enzymes cystathionine-β-synthase (CBS), cystathionine-γ-lyase (CSE) and 3-mercaptopyruvate sulfurtransferase (MPST). We demonstrated that H(2)S-producing enzymes are active in porcine oocytes and that a statistically significant decline in endogenous H(2)S production occurs during the first day of aging. Inhibition of these enzymes accelerates signs of aging in oocytes and significantly increases the ratio of fragmented oocytes. The presence of exogenous H(2)S from a donor (Na(2)S.9H(2)O) significantly suppressed the manifestations of aging, reversed the effects of inhibitors and resulted in the complete suppression of oocyte fragmentation. Cultivation of aging oocytes in the presence of H(2)S donor positively affected their subsequent embryonic development following parthenogenetic activation. Although no unambiguous effects of exogenous H(2)S on MPF and MAPK activities were detected and the intracellular mechanism underlying H(2)S activity remains unclear, our study clearly demonstrates the role of H(2)S in the regulation of porcine oocyte aging.